Bronze decoration for chariots in Northern Italy (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2010)
A list of the bronze decoration (only figural) for roman chariots in Northern Italy has been collected. The query, even though probably non complete, produced an outstanding increase of the known objects (now about fifty), allowing some remarks about workshops, owners, iconography, cronology.
Keywords: bronze; figural decoration; chariots